Dynamics of KRas on endosomes: involvement of acidic phospholipids in its association. Issue 7 (9th April 2014) - Gelabert‐Baldrich, Mariona; Soriano‐Castell, David; Calvo, Maria; Lu, Albert; Viña‐Vilaseca, Arnau; Rentero, Carles; Pol, Albert; Grinstein, Sergio; Enrich, Carlos; Tebar, Francesc
ABSTRACT: The endocytic compartment is emerging as a functional platform for controlling important cellular processes. We have found that 10 to 15% of total KRas, a protein that is frequently mutated in cancer, is present on endosomes, independent of its activation state. The dynamics of GFP‐KRas wild‐type (WT) and constitutively active or inactive mutants on endosomes were analyzed by fluorescence recovery after photobleaching (FRAP) microscopy. The measurements revealed an extraordinarily fast recovery of KRas WT [half‐time (HT), 1.3 s] compared to HRas, Rab5, and EGFR, with the active KRasG12V mutant being significantly faster and more mobile (HT, 1 s, and 82% of exchangeable fraction) than the inactive KRasS17N (HT, 1.6 s, and 60% of exchangeable fraction). KRas rapidly switches from the cytoplasm to the endosomal membranes by an electrostatic interaction between its polybasic region and the endosomal acidic phospholipids, mainly phosphatidylserine.—Gelabert‐Baldrich, M., Soriano‐Castell, D., Calvo, M., Lu, A., Viña‐Vilaseca, A., Rentero, C., Pol, A., Grinstein, S. Enrich, C., Tebar, F. Dynamics of KRas on endosomes: involvement of acidic phospholipids in its association. FASEB J . 28, 3023–3037 (2014). www.fasebj.org